Dihydromyricetin improves growth performance, immunity, and intestinal functions in weaned pigs challenged by enterotoxigenic Escherichia coli - Xie, Kunhong; Qi, Jiawen; Deng, Lili; Yu, Bing; Luo, Yuheng; Huang, Zhiqing; Mao, Xiangbing; Yu, Jie; Zheng, Ping; Yan, Hui; Li, Yan; Li, Hua; et al. (Frontiers in Veterinary Science, 2024)
In contemporary agriculture, artificially reared early-weaned piglets are feeding diets containing antibiotics to relieve diarrhea and intestinal injury in pig production.However, the pharmaceutical use of antibiotics is prohibited by the legislation of several countries due to potential health and environmental concerns. Hence, there is an urgent need for developing alternatives to traditionally used antibiotics to help improve the performance or improve structure and function of the gastrointestinal tract, then inhibit the incidence of diarrhea induced by Escherichia coli (ETEC) challenge in pigs. Dihydromyricetin (DMY) is a natural flavanonol compound extracted from Ampelopsis grossedentata with numerous biological activities such as antioxidative and immunomodulatory functions. The aim of this study was to investigate the effects of DMY on growth performance, immunity, and intestinal barrier functions in weaned pigs upon enterotoxigenic Escherichia coli challenge. In conclusion, dietary DMY can alleviate the intestinal injury in weaned pigs upon ETEC challenge and can be served as a natural potent substitute for antibiotics.Teaser Text: Dihydromyricetin supplementation could improve the growth performance and enhanced the intestinal functions in weaned pigs.